The prevalence of gastrointestinal parasites in wild rats (muridae) in pilajau oil palm plantation of Sawit Kinabalu Group, Membakut Sabah Malaysia / Richel Natasha Frederick and Siti Sarayati Abdul-Mawah - Frederick, Richel Natasha; Abdul-Mawah, Siti Sarayati (Universiti Teknologi MARA, Sabah, 2022)
Rats are pests and reservoirs for ectoparasites and endoparasites. This study was conducted at the Pilajau oil palm plantation to evaluate the prevalence of gastrointestinal parasite infection among wild rats. This study identified the rat species and sex based on its morphological characteristics. Gastrointestinal parasites were identified up to the genus level using formalin-ether concentration (FECT). Parasite eggs and oocysts were quantified with a modified McMaster method using Sheather's solution. The plantation rats included Rattus rattus and Rattus norvegicus. There were more captured males (60%) than females (40%) of R. norvegicus and R. rattus. This study also discovered a total of 11 parasite genera, and only one non-zoonotic genus, Eimeria spp. Most of the identified nematodes, cestodes and protozoa parasites were zoonotic. Additionally, the prevalence and mean intensity of parasite infection in wild rats were also calculated. Strongyloides spp. (100%) recorded the highest prevalence in wild rats, followed by Nippostrongylus spp. (86.67%), Ancylostoma spp. (76.67%), Blastocystis spp. (76.67%), Trichuris spp. (70%), Eimeria spp. (60%), Ascaris spp. (50%), Capillaria spp. (46.67%), Entamoeba spp. (33.33%) and Cryptosporidium spp. (26.67%). In terms of intensity, most readings obtained were below 500 EPG, which is suggestive of mild parasitic infection in wild rats. However, due to its zoonotic potential, workers and residents living near the plantation area are still exposed to zoonotic pathogens transmitted by wild rats.